Front Cover Picture: Diastereospecific Bis‐alkoxycarbonylation of 1, 2‐Disubstituted Olefins Catalyzed by Aryl α‐Diimine Palladium(II) Catalysts (Adv. Synth. Catal. 18/2018). Issue 18 (5th June 2018) - Olivieri, Diego; Fini, Francesco; Mazzoni, Rita; Zacchini, Stefano; Della Ca', Nicola; Spadoni, Gilberto; Gabriele, Bartolo; Mancuso, Raffaella; Zanotti, Valerio; Carfagna, Carla
Abstract : Thefront cover picture supplied by Carla Carfagna and co‐workers depicts an efficient process for the diastereospecific bis‐alkoxycarbonylation of 1, 2‐disubstituted olefins, leading to the synthesis of 2, 3‐disubstituted‐succinic diesters. Using Pd(TFA)2 as palladium source, bis‐(2, 6‐dimethylphenyl)‐2, 3‐dimethyl‐1, 4‐diazabutadiene as ligand and p ‐benzoquinone as oxidant, aliphatic, aromatic, cyclic olefins and unsaturated fatty acid methyl esters, have been successfully converted in the presence of different alcohols, under mild reaction conditions ( P CO =4 bar, T =20 °C). Further details can be found in the full paper on pages 3507–3517 (D. Olivieri, F. Fini, R. Mazzoni, S. Zacchini, N. Della Ca′, G. Spadoni, B. Gabriele, R. Mancuso, V. Zanotti, C. Carfagna, Adv. Synth. Catal .2018, 360, 3507–3517: DOI10.1002/adsc.201701597 ).